4 - Brazil, Russia, India, China, and South Africa (BRICS) and Africa: New Projected Developmental Paradigms - Lumumba-Kasongo, Tukumbi (Africa Development, 2021)
This article reflects on the dynamics of the Brazil, Russia, India, China and South Africa (BRICS) states’ political economy and its implications for Africa’s continuous effort to search for new developmental paradigms. The core questions addressed in the article are: What are the BRICS states specifically proposing to the existing world order and the global south in the areas of paradigms of economic and social development and systems of governance? What do these countries have in common? Can this commonality be instrumentalised and converted in favour of African progress? What is the ideological foundation of their solidarity? Within the pragmatism and ideology related to this solidarity, are the BRICS states proposing new development schemes to replace the failed old, top-down, anarchical, market-based, linear, and one-size-fits-all model of social and economic development? Based on the dynamics of the BRICS grouping and the movements of its members, it is argued that the emerging markets and economies in the Global South, regardless of the ideological contradictions and internal structural political weaknesses among its members, implies that the business-as-usual approach in the practices of the institutions of international political economy and world politics is no longer the only pragmatic way of conducting business. To have a significant impact in Africa, BRICS’s activities should be shaped and guided by the bottom-up perspectives. BRICS strongly calls for shifts of paradigms in the realm of the world power and for qualitative state intervention in the management of the invisible hand of Adam Smith.